Pengaruh Promosi Online dan Ketersediaan Fasilitas Terhadap Minat Sewa Bus Pariwisata di PT. Berdikari Artha Jaya - Riswarnanda, Alfito; Anandita, Septian Ragil (Fakultas Ekonomi Universitas KH. A. Wahab Hasbullah, 2025)
This study examines the influence of online promotion and facility availability on the rental interest of tourist buses at PT. Berdikari Artha Jaya. This topic is important due to the rapid growth of internet users in Indonesia and the increasing role of digital promotion in the transportation business. The novelty of this research lies in directly testing the combined effects of online promotion and facility availability on rental interest in a bus company still operating a semi-manual system. The method used is correlational quantitative research with primary data collected through questionnaires distributed to 138 customers. Regression analysis shows that online promotion significantly affects rental interest, while facility availability does not have a significant individual effect, but together they significantly influence rental interest. The conclusion is that effective online promotion strategies are crucial to increasing rental interest, while facility improvements remain essential to maintain customer satisfaction. The implications of this research encourage digital marketing development and service quality enhancement in the tourist bus rental business.